2018
DOI: 10.1021/acsami.8b14172
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Performance of Ir Species by Employing TiN as the Support toward Oxygen Evolution Reaction

Abstract: Reducing the noble-metal loading without sacrificing the catalytic performance of the oxygen evolution reaction (OER) catalysts is paramount yet highly challenging. Herein, IrO2@Ir/TiN electrocatalysts employing TiN as the support have been developed and shown high efficiency toward OER. TiN is found not only to disperse the IrO2@Ir nanoparticles effectively but also to exert the electronic modulation of Ir by downshifting its d-band center of 0.21 eV compared to pure IrO2. Excitingly, TiN remarkably enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 54 publications
2
85
0
Order By: Relevance
“…For example, Ir nanoparticles can be well dispersed onto the TiN carrier. The IrO2@Ir/TiN catalyst prepared by Xing's group showed an enhanced catalytic performance [50]. The overpotential was only 265 mV at a current density of 10 mA•cm −2 .…”
Section: Metal-support Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ir nanoparticles can be well dispersed onto the TiN carrier. The IrO2@Ir/TiN catalyst prepared by Xing's group showed an enhanced catalytic performance [50]. The overpotential was only 265 mV at a current density of 10 mA•cm −2 .…”
Section: Metal-support Interactionmentioning
confidence: 99%
“…Ir-based catalysts also suffer similar degradation issues [49]. During the long-term catalytic process, rutile oxide of IrO x will transition to other kinds of phases that are soluble in acid media [50]. Therefore, the harsh operating conditions must be taken into account when designing suitable catalysts.…”
Section: H O L → O + 4h + 4ementioning
confidence: 99%
See 1 more Smart Citation
“…[142] More importantly, to further reduce the noble metal usage, a series of substrates, including carbon, graphene, metal nitrides (e. g., Fe 4 N, TiN), and antimony-doped tin oxide (ATO), have been widely used as support for Ru and/or Ir nanomaterials due to their high surface area, good electroconductivity, and excellent stability. [146][147][148][149][150] For instance, Tackett et al designed a unique core-shell structure with iridium/metal nitride morphology. Owing to the typical core-shell structure, the Ir mass activity in the iridium/metal nitride material exhibits 2.0 times higher than that of commercial IrO 2 .…”
Section: Pure Noble Metal Nanomaterialsmentioning
confidence: 99%
“…showed that IrO 2 @Ir on TiN (IrO 2 @Ir/TiN) featured stable OER performance in 0.50 m H 2 SO 4 . [ 95 ] When tested by CP, IrO 2 @Ir/TiN showed stable OER activity with only a 17.6 mV increase of overpotential after 6 h of operation. ICP‐optical emission spectroscopy (OES) showed the Ir dissolution of the IrO 2 @Ir/TiN with less than half of that of the unsupported IrO 2 @Ir, indicating the effective role of TiN to the preservation of Ir from dissolution (Figure 11e).…”
Section: Engineering and Fabrication On The Electrodes For The Long‐tmentioning
confidence: 99%